The position of Aristotle, Avicenna, and Al- Farabi on divine science - Alhusen, Munerah Sulaiman (Journal of Islamic Sciences, 2021)
Atheism has abounded in the names and attributes of God with a departure from the age of prophethood. It is atheism that philosophers call it positive by itself, or the effective cause, or the active intellect. In this paper I will discuss- God willing- I will discuss the description of knowledge for God and explain their mistakes and methodology Followed in this research: Inductive- Comparative ApproachThe most important results that I reached: that the first person to speak about the issue of divine science was Aristotle, and Al- Farabi and Ibn Sina attempted to reconcile between Aristotle's words and Sharia, denying God's knowledge of the details, and Al- Ghazali and Sheikh al- Islam's response to the speculations of the philosophers, and that the comparison that the Sheikh chief made between human science and science The divine reveals to us that this divine knowledge is free from the change and deficiency that we find in human knowledge, there is no evidence for Ibn Sina's disagreement with the speakers on this issue as in other issues, and the research was divided into an introduction, three chapters, investigations and a conclusion.
Keywords: Divine knowledge; Philosophy; Aristotle; Ibn Sina; Al- Farabi